MON-520 Symptoms, Comorbidities, and Treatment Satisfaction with Chronic Hypoparathyroidism: Findings from a 13-Country Patient Survey - Bollerslev, Jens (J Endocr Soc, 2019)
Hypoparathyroidism (HypoPT) is a rare disorder managed by conventional therapy of oral calcium and vitamin D; however, some patients on therapy remain symptomatic. We report results from a global patient survey (13 countries) to assess burden of illness associated with HypoPT. An anonymous survey was conducted in patients with uncontrolled chronic HypoPT (as determined by patients’ reports of persistent symptoms and/or poorly controlled calcium levels as told by their physician) despite receiving conventional therapy. Patients currently or previously treated with parathyroid hormone were excluded. HypoPT-associated symptoms were assessed through disease-specific Hypoparathyroidism Symptom Diary (HypoPT-SD). All analyses were descriptive. Survey was conducted Oct 2017─Mar 2018 in 398 patients who met study inclusion criteria (mean age, 51.7 years; women, 78%; surgery as main cause of HypoPT, 80%; mean duration of HypoPT, 8.9 years), of whom 91% reported persistent symptoms despite treatment and 67% had been told by a physician that their calcium levels were poorly controlled. Self-perceived overall symptom severity was reported by patients as severe (12%), moderate (53%), mild (32%), or none (3%). Per HypoPT-SD, patients reported symptoms of physical fatigue (97%), muscle cramps (86%), tingling (84%) and heaviness in limbs (82%), and cognitive and mood symptoms of brain fog (77%), anxiety (78%), and depression (76%). Frequently reported comorbidities were hypertension (41%); mental, behavioral, or neurodevelopmental disorders (29%); arrhythmia (28%); kidney problems (27%) [kidney stones/calcification/impaired function, 18%; chronic kidney disease, 7%; kidney failure, 2%]; infections (18%); diabetes (17%); and decreased bone mineral density (17%). Impact on daily life, rated as “somewhat” or “very much”, was reported by 84% of patients for ability to exercise, 78% for sleep, 75% for ability to work, and 63% for family relationships. Most patients (96%) reported that their HypoPT was not controlled on current medication. Over half of these patients (53%) disagreed with their physician’s judgement that the current medication provided adequate control of their disease. Findings from this global survey demonstrated that uncontrolled chronic HypoPT can be associated with substantial burdensome symptoms, comorbidities, and impact on various aspects of daily living, with more than half of the patients reporting moderate to severe symptom levels and dissatisfaction with conventional therapy. Disclosures: JB and HS: advisory board member and speaker for Shire; BLC: consultant for Shire; JG, CM, and KC: employees of Shire; HD-H: no conflicts; EG: volunteer with Hypopara UK (donations received from Shire); NB-E, DJ, and KG: employees of Adelphi Real-World (contracted by Shire). Funding: Shire